Pengembangan Buku Ajar Pendidikan Agama Kristen bagi Anak Katekisasi Gereja Menggunakan Model ADDIE untuk Membentuk Karakteristik Kristiani di Era Digital - Selderika Patty; Christiana D W Sahertian (Lembaga Teewan Journal Solutions, 2026)
The development of digital technology has significantly influenced the lives of young people, particularly in education and character formation. As a faith-based educational institution, the church is responsible for preparing the younger generation to live according to Christian values amid the challenges of the digital era. Catechism plays a vital role in nurturing faith, yet the limited availability of engaging and relevant teaching materials often reduces the effectiveness of the learning process. This study aims to develop a Christian Religious Education textbook for church catechism students using the ADDIE model, which includes the stages of Analysis, Design, Development, Implementation, and Evaluation. The research employed a Research and Development (R&D) approach to design, validate, and evaluate the textbook. The findings demonstrate that the developed textbook improves participants’ understanding of Christian faith, increases learning participation, and supports the development of Christian character, including love, honesty, responsibility, discipline, and social concern. Furthermore, the textbook provides systematic, contextual, and relevant learning resources that align with the needs and learning characteristics of the digital generation. Therefore, the developed textbook is an effective alternative learning resource for church catechism ministry and contributes to strengthening faith formation and Christian character development among catechism participants.